The Controversy Surrounding the Arcade of Struthers: A Systematic Review of Literature - Tinatin Natroshvili; Maaike van de Meene; Walter J. Szweryn; Marius A. Kemler (Indian Journal of Plastic Surgery)
The arcade of Struthers was first described by Kane et al in 1973 as a thickening of the deep investing fascia of the distal arm and superﬁcial ﬁbers of the medial head of the triceps muscle extending to the medial intermuscular septum. However, existence of anatomical structure remains disputed, lacking a unanimous consensus. This systematic review aims to provide an overview of all findings and conclusions on this subject. A literature search was conducted using Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medline, Embase, and Web of Science. The QUality Appraisal for Cadaveric Studies (QUACS) scale was used for quality appraisal. In total, 12 studies (including 348 arms) agreed with the existence of the arcade of Struthers and its role in ulnar nerve entrapment. One study agreed with the existence of the structure, but disagreed with its nomenclature. On the other side, five studies (describing 224 arms) were against the existence of the structure. In literature, studies can be divided into two groups. The first group agrees with the existence of the arcade of Struthers as described by Kane et al in 1973, emphasizing its role in ulnar nerve entrapment. The second group disagrees with the existence of the arcade of Struthers, and is further divided into those who believe the structure is best described as an accessory origin of the head of the triceps muscle and those who consider it a dissection artifact.